Modern playhouses an architectural history of Britain's new theatres, 1945-1985 - Fair, Alistair (Oxford University Press, 2018)
A detailed study of the major programme of theatre-building in Britain between the 1950s and the 1980s, this book draws on a vast range of archival material to present the history of post-war theatre buildings as a history of ideas relating not only to performance but also to culture, citizenship, and the modern city